2013
DOI: 10.1056/nejmoa1212793
|View full text |Cite
|
Sign up to set email alerts
|

A Trial of Imaging Selection and Endovascular Treatment for Ischemic Stroke

Abstract: BACKGROUND Whether brain imaging can identify patients who are most likely to benefit from therapies for acute ischemic stroke and whether endovascular thrombectomy improves clinical outcomes in such patients remains unclear. METHODS In this study, we randomly assigned patients within 8 hours after the onset of large-vessel, anterior-circulation strokes to undergo mechanical embolectomy (Merci Retriever or Penumbra System) or receive standard care. All patients underwent pretreatment computed tomography or m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
852
3
40

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 1,271 publications
(907 citation statements)
references
References 22 publications
12
852
3
40
Order By: Relevance
“…This choice was driven by the findings of SWIFT and TREVO-2, two head-to-head randomized clinical trials comparing the reperfusion performance of stent retrievers against the MERCI device, where stent retrievers yielded a four-times higher chance of post-procedure reperfusion and higher rates of good clinical outcome 32,33 . Indeed, prior trials that did not show benefit of endovascular treatment used other first generation mechanical thrombectomy devices (mainly the MERCI device) or intra-arterial injection of TPA 21,22,34 . One assumed reason for the absence of clinical benefit in those earlier trials was the low rate of successful reperfusion.…”
Section: Considerations On Patient Selection and Endovascular Intervementioning
confidence: 99%
“…This choice was driven by the findings of SWIFT and TREVO-2, two head-to-head randomized clinical trials comparing the reperfusion performance of stent retrievers against the MERCI device, where stent retrievers yielded a four-times higher chance of post-procedure reperfusion and higher rates of good clinical outcome 32,33 . Indeed, prior trials that did not show benefit of endovascular treatment used other first generation mechanical thrombectomy devices (mainly the MERCI device) or intra-arterial injection of TPA 21,22,34 . One assumed reason for the absence of clinical benefit in those earlier trials was the low rate of successful reperfusion.…”
Section: Considerations On Patient Selection and Endovascular Intervementioning
confidence: 99%
“…In the acute setting, the recently reported DEFUSE II (Diffusion and Perfusion Imaging Evaluation for Understanding Stroke Evolution II) trial showed the feasibility of using magnetic resonance imaging (MRI) to perform rapid and reliable triage of patients for thrombolytic therapy. 5 In contrast, the MR-RESCUE (Mechanical Retrieval and REcanalization of Stroke Clots Using Embolectomy) clinical trial 6 showed inconclusive results for the use of imaging in the acute stroke setting. Thus, the dependence of perfusionweighted/diffusion-weighted imaging mismatch for triage has led to both positive and negative results in large multicenter trials.…”
Section: Introductionmentioning
confidence: 99%
“…Three recent, simultaneous publications report the neutral results of three randomized studies (SYNTHESIS Expansion, Interventional Management of Stroke (IMS) III, and Mechanical Retrieval and Recanalization of Stroke Clots Using Embolectomy (MR RESCUE)) comparing IV thrombolysis therapy or standard care (MR RESCUE) to the endovascular treatment (EVT) of acute ischemic stroke (AIS) [1][2][3]. The results of these three trials might lead to the erroneous conclusion that endovascular treatment has no or little place in the management of AIS.…”
Section: Introductionmentioning
confidence: 99%